(untitled) (Journal of Orofacial Research, 1970)
Friction between the archwire and brackets is one of the major determinant of tooth movement in preadjusted edgewise appliance. The aim of the present study was to evaluate the differences in the frictional forces among low-friction ligation modules, conventional ligation and self-ligation systems with stainless brackets and ceramic brackets. Stainless steel (SS), Damon self-ligating and ceramic brackets of 0.022" × 0.028" slots 5 to 5 to represent the upper right to the upper left second bicuspid were used. Archwires used were 0.016" NiTi-straight length 18 cm long and 0.019" × 0.025" SS-straight length 18 cm long, and slide low-friction ligatures and alastik modules were used. The testing apparatus consisted of a friction-testing device, Instron universal testing instrument, load cell, signalamplifier and computer. The mean and standard deviation (SD) were calculated. The mean values were compared by one-way ANOVA. Multiple range tests by Tukey-Kramer honest significant difference (HSD) procedures were employed to identify the significant groups if p-value in one-way ANOVA is significant by using statistical software. The results showed that conventional ligation exhibited higher fiction than low-friction and self-ligation with all the archwire-bracket combinations. Damon self-ligating system exhibited less friction than lowfriction ligation with lower archwires and higher friction with higher archwires.